2008
DOI: 10.1080/10826060701885126
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Structure Analysis of Antifreeze Proteins fromAmmopiptanthus mongolicus

Abstract: We purified many kinds of antifreeze proteins with high activity from the leaves of Ammopiptanthus mongolicus by several biochemical techniques. The antifreeze activities of these AFPs were measured by both osmometry and differential scanning calorimetry, and the inhibition of growth of ice crystals by the AFPs was obvious. Additionally, the antifreeze proteins were analyzed by sequencing, glycosylation reaction, mass spectroscopy, and circular dichroism spectroscopy. Both samples have some other unique struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
0
11
1
Order By: Relevance
“…Therefore, the discrepancy between electrophoretic and mass spectrometry data is likely a direct consequence of the structure of the AFP; perhaps it contains modified groups that cannot be extrapolated. The A. nanus AFP was larger than reported for A. mongolicus (Jiang et al 1999;Fei et al 2000), perhaps also due to some modified groups.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Therefore, the discrepancy between electrophoretic and mass spectrometry data is likely a direct consequence of the structure of the AFP; perhaps it contains modified groups that cannot be extrapolated. The A. nanus AFP was larger than reported for A. mongolicus (Jiang et al 1999;Fei et al 2000), perhaps also due to some modified groups.…”
Section: Discussioncontrasting
confidence: 45%
“…The presence of AFPs is widespread in antifreeze organism, including fish (DeVries and Wohlschlag 1969; Davies and Hew 1990;Evans and Fletcher 2004), plants (Griffith et al 1992;Urrutia et al 1992;Sidebottom et al 2000;AtIcI and Nalbantog˘lu 2003), insects (Zachariassen and Husby 1982; Abbreviations: AFP, antifreeze protein; THA, thermal hysteresis activity; DSC, differential scanning calorimetry; BSA, bovine serum albumin; HDMS TM , high definition mass spectrometry 2004), fungi and bacteria (Duman and Olsen 1993;Gilbert et al 2004). A previous publication by Fei (2000) indicated that AFPs were produced in A. mongolicus leaves during winter, which decreases the freezing temperature of body fluids non-colligatively (Griffith and Yaish 2004). It is not known, however, whether A. nanus also exhibits the same freezing resistant characteristic.…”
mentioning
confidence: 99%
“…AmEBP1 was able to promote the induction of KIN1, COR15A, and other cold-inducible genes. Because woody perennials must survive long-term freezing temperatures in winter, many need to have developed AFPs and other cold responsive proteins to lower the freezing point of plant issues and to protect plants against frost damage, such as Prunus persica and A. mongolicus (Wisniewski et al 1999;Fei et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Dozens of antifreeze proteins (AFPs) with high thermal hysteresis activity (THA) have been purified and characterized (Fei et al 2008). In this study, our intent was to discover and analyze a battery of genes closely associated with FT in A. Mongolicus.…”
Section: Introductionmentioning
confidence: 99%
“…Both samples expressed some other unique structures different from those of fish and insects. It was suggested that plant AFPs might have a particular antifreeze mechanism in comparison with that of fish and insects (Fei et al, 2008).…”
Section: Introductionmentioning
confidence: 99%